2016
DOI: 10.1021/acs.jpcc.5b11496
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Site Symmetry, Spin State, and Doping Concentration for Co(II) or Co(III) in β-NaYF4

Abstract: Magnetic dopants provide versatile tunability of properties for transparent host matrix materials, semiconductors, and nanostructured materials. The relationship between doping concentration, site symmetry, crystal-field splitting, and spin state for Co(II) and Co(III) doped in hexagonal-phase NaYF 4 crystals and nanocrystals was investigated in a spin-polarized density functional theory approach. With decreasing dopant concentrations, the geometry of the Co(II) fluoride nearest-neighbor coordination changes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…For each plot in Figure (a)–(f) the RDF is plotted for the optimized, neutral ground state (black, solid), singlet (green, dash–dash), doublet (red, dot-dot), and triplet (blue, dot-dash) spin configuration for the optimized polaron geometries. Increases (decreases) in peaks of the RDF between the neutral ground state and PGS can be associated with increases (decreases) in coordination number of ions due to polaron formation. Shifts in RDF peaks along the x -axis would correspond to average bond/coordination elongation or contraction.…”
Section: Resultsmentioning
confidence: 99%
“…For each plot in Figure (a)–(f) the RDF is plotted for the optimized, neutral ground state (black, solid), singlet (green, dash–dash), doublet (red, dot-dot), and triplet (blue, dot-dash) spin configuration for the optimized polaron geometries. Increases (decreases) in peaks of the RDF between the neutral ground state and PGS can be associated with increases (decreases) in coordination number of ions due to polaron formation. Shifts in RDF peaks along the x -axis would correspond to average bond/coordination elongation or contraction.…”
Section: Resultsmentioning
confidence: 99%
“…CaCo 3 V 4 O 12 features a combination of several dissimilar and potentially competing electronic effects, including strong Coulomb correlations, spin–orbit coupling, and orbital polarization, thus posing a daunting challenge for ab initio calculations and making this compound an interesting system for experimental studies. Other calculations showed that even Co 2+ dopants with the square-planar coordination can essentially modify the electronic band structure of materials …”
Section: Introductionmentioning
confidence: 99%
“…Other calculations showed that even Co 2+ dopants with the squareplanar coordination can essentially modify the electronic band structure of materials. 46 In this work, we synthesized high-quality single crystals of CaCo 3 V 4 O 12 perovskite and examined the evolution of its structural, vibrational, and transport properties upon strong compression to 60 GPa. We found a crossover near 30 GPa, above which the Co−O bonds in the square-planar oxygen planes demonstrated an abnormally high compressibility.…”
Section: ■ Introductionmentioning
confidence: 99%